On enhancement and control of green emission of rare earth co-doped hydroxyapatite nanoparticles: synthesis and upconversion luminescence properties. (22nd December 2020) - Nhu Van, Hoang; Le Manh, Tu; Do Thi Thuy, Dung; Pham, Vuong-Hung; Nguyen, Duy-Hung; Pham Thi Hong, Diep; Van Hung, Hoang
Abstract : In this work, low-temperature hydrothermal synthesis of a series of x Mo–1%Er–10%Yb ( x :mol%) doped hydroxyapatite (HA) phosphors was studied. Abstract : In this work, low-temperature hydrothermal synthesis of a series of x Mo–1%Er–10%Yb ( x :mol%) doped hydroxyapatite (HA) phosphors was studied. The single phase of hexagonal structure HA nanorods obtained with high crystallinity was verified using characterization techniques such as XRD and HRTEM + SAED. It was found that the presence of the orientation associated with near to the 210 planes of the HA phase was favored with the increase of the Mo 6+ doping content and different hydrothermal reaction times. The Mo 6+ doped HA:Er-Yb phosphor showed an energetic green UC emission band (520/550 nm) and weak red UC emission band (655 nm) attributed to ( 2 H11/2, 4 S3/2 )– 4 I15/2, 4 F9/2 – 4 I15/2 transition of the Er 3+ ion, respectively, under 975 nm laser excitation. Notably, the green emission intensity of the Mo 6+ doped phosphor is 70 times higher than that of the samples without doped Mo 6+ content. The high efficiency of the green UC can be attributed to the novel energy transfer process from the | 2 F7/2, 3 T2 〉 state of the Yb 3+ –MoO4 2− dimer to the 4 F7/2 of the Er 3+ ions. The results from fitting the theoretical model to the experimental luminescence decay curves of the undoped and doped samples showed that the decay time of green emission of the sample doped with Mo 6+ ions (329 μs) is longer than that of the undoped sample (299 μs), which confirms the presence of the Yb 3+ –MoO4 2− dimer in the system. Moreover, the grain orientations due to the effect of Mo 6+ ions doped in the HA phosphor could favor the enhancement of the UC emission intensity. The UC mechanism of Mo 6+ doped HA:Er-Yb was determined to be three (green band) and two photon (red band) absorption processes. The results suggest that the HA:Er–Yb–Mo phosphor could have potential in solar cell and biomedical applications.